Carers and Careers. Grandparental care investment and its labour market consequences in Europe - Zanasi, Francesca (Università degli studi di Trento, 2020)
As life expectancy increases, grandparents spend a longer part of their life with grandchildren, which opens opportunities for sharing time, resources, and affection. The present dissertation aims at investigating the content of the grandparent-grandchild relationship and, at the same time, the consequences that becoming a grandmother could have on mid-life women’s labour market participation. It revolves around three main contributions. First, it approaches grandparenting from a stratification perspective, putting forward that grandparents could perform different activities with grandchildren according to their educational levels. Second, it investigates grandmothers’ transition to retirement as driven by the institutional context, which shapes both the extent to which grandparental childcare is needed as support for the younger generations (measured through the availability of childcare services) and the extent to which it is easy and attractive to withdraw early from the labour force for old-age individuals (measured through the generosity of the pension system). Finally, it considers grandmothers’ labour market withdrawal as enabled, or constrained, by women’s previous work history, with two case-studies: England and Italy. In fact, decisions taken earlier in life on work-family reconciliation, on the one hand, could be reproduced in late-life upon the grandchild’s birth; on the other hand, years worked, and kind of job held open different routes for retirement. Taken together, the present dissertation unveils that grandparenthood is a multifaceted phenomenon, which must be studied in a multi-generational framework and by considering demographic, social, and institutional trends of current European societies.